Impact of Institutionalization in Family-Owned Companies and Elements of Intellectual Capital on Competitive Power: a Research on Family-Owned Hospitality Businesses - Türkoğlu, Nuray (Muş Alparslan Üniversitesi, 2018)
In this study, it has been aimed to examine the impact ofinstitutionalization and intellectual capital elements on administrative pointof view and competitive power in hospitality businesses owned by a family. Thesample of research has been determined as the directors of four or five-starhospitality businesses owned by families, which are carrying out an activity inAntalya city located within the boundaries of Mediterranean Region of Turkey.Data has been gathered by using the stratified sampling method with a surveyform with 5 point graduation. As a result of data analysis, while no meaningfulinteraction between formalization in family-owned businesses and competitivepower, it has been observed that organizational culture, customers and structuralcapital have positive impact on competitive power.

Buçalışmada aile işletmesi olan konaklama işletmelerinde kurumsallaşma veentelektüel sermaye unsurların yönetici bakış açısı ile rekabet gücüneetkisinin incelenmesi amaçlanmıştır. Araştırma örneklemi, Türkiye’ de AkdenizBölgesi sınırları içerisinde yer alan Antalya ilinde faaliyet gösteren dört vebeş yıldızlıaile işletmesi olan konaklama işletmeleri yöneticileri şeklindebelirlenmiştir. Veriler 5’li derecelemeyesahip anket formu ile tabakalıörnekleme kullanılarak toplanmıştır. Toplamda 210 anket formu elde edilmiştir.Verilerin analizi sonucunda aile işletmelerinde formalleşme ve insan sermayesiile rekabet gücü arasında anlamlı etkileşim bulgulanmazken, örgüt kültürü ilemüşteri ve yapısal sermayenin rekabet gücünüpozitif anlamda etkilediği görülmüştür.
Aile İşletmesi Niteliğindeki Şirketlerdeki Kurumsallaşmanın ve Entellektüel Sermayenin Rekabet Gücü Üzerindeki Etkisi: Aile İşletmesi Niteliği Taşıyan Konaklama İşletmelerinde Bir Araştırma
anemon
Keywords: Institutionalization; Intellectual Capital; Competitive Power; Family-owned Businesses; Hospitality Businesses; Kurumsallaşma; Entelektüel Sermaye; Rekabet Gücü; Aile İşletmeleri; Konaklama İşletmeleri